A Case Report on Frontal Osteoma (Pulse, 2017)
A 13 years old boy admitted with the complaint of progressive exophthalmos and gradually decreasing vision on right eye, also occasional headache and deformity on the right fronto-orbital region. Radiological & clinical findings revealed a case of frontal osteoma in the right frontal sinus extending up to right frontal lobe, eroding right roof of the orbit. Complete excision of the tumor mass was possible surgically. Biopsy confirmed a case of osteoma. Below is a discussion on diagnosis & management of frontal osteomaPulse Vol.9 January-December 2016 p.45-48